2021
DOI: 10.1016/j.jpsychores.2021.110399
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of post-traumatic stress symptoms, anxiety, and depression in hospitalized COVID-19 patients: A one-month follow-up

Abstract: Objectives Little is known about the mental health outcomes of hospitalized COVID-19 patients. The aims of the study were: (1) to examine the trajectories of anxiety, depression, and pandemic-related stress factors (PRSF) of COVID-19 hospitalized patients one-month following hospitalization; (2) to assess the presence of post-traumatic stress symptoms (PTSS) a month after hospitalization; (3) to identify baseline risk and protective factors that would predict PTSS one month after hospitalization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 18 publications
7
82
0
1
Order By: Relevance
“…Depression is significantly higher than controls until 30 days after recovery whereafter the symptoms improve and no significant differences between cases and controls were found. Matalon et al (2021) reported that depression and anxiety had normalised at the one month follow-up, but were predictors of longer lasting PTSD. Mazza et al (2021) found persistent depressive symptomatology at 3 month follow-up, whereas anxiety had improved at this timepoint.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depression is significantly higher than controls until 30 days after recovery whereafter the symptoms improve and no significant differences between cases and controls were found. Matalon et al (2021) reported that depression and anxiety had normalised at the one month follow-up, but were predictors of longer lasting PTSD. Mazza et al (2021) found persistent depressive symptomatology at 3 month follow-up, whereas anxiety had improved at this timepoint.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently reported psychiatric deficits were depression and/or anxiety. In total, this was examined in 47 studies ( Al-Aly et al, 2021 , Alemanno et al, 2021 , Boari et al, 2021 , Chen et al, 2020 , Chevinsky et al, 2021 , Daher et al, 2020 , Darley et al, 2021 , Daugherty et al, 2021 , De Lorenzo et al, 2020 , Frontera et al, 2021 , Gennaro et al, 2021 , González et al, 2021 , Halpin et al, 2021 , Huang et al, 2021a , Iqbal et al, 2021 , Lorenzo et al, 2021 , Matalon et al, 2021 , Mattioli et al, 2021 , Mazza et al, 2020 , Mazza et al, 2021 , Méndez et al, 2021 , Monti et al, 2021 , Morin et al, 2021 , Negrini et al, 2021 , Noviello et al, 2021 , Ortelli et al, 2021 , Poyraz et al, 2021 , Romero-Duarte et al, 2021 , Sykes et al, 2021 , Tanriverdi et al, 2021 , Taquet et al, 2021a , Taquet et al, 2021b , Tomasoni et al, 2021 , Townsend et al, 2021 , van den Borst et al, 2020 , Venturelli et al, 2021 , Wang et al, 2020b , Wang et al, 2020c , Whiteside et al, 2021 , Wong et al, 2020 , Wu et al, 2020 , Xiong et al, 2021 , Yuan et al, 2020 , Zhou et al, 2020 , D'Cruz et al, 2021 , de Graaf et al, 2021 , Weerahandi et al, 2021 ). The results range from no indication of depression or anxiety ( Daher et al, 2020 , Zhou et al, 2020 ) to >30% at follow-up ( De Lorenzo et al, 2020 , Frontera et al, 2021 , Iqbal et al, 2...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have been performed to evaluate post-traumatic stress symptoms in the general population, though [ 5 ]. A study that had addressed the prevalence of PTSD among COVID recovered patients found that nearly 20% of these patients had symptoms of post-traumatic stress 1 month following hospitalization [ 7 ]. However, this study does not have a good representation of older adults above 65 years, who are the most vulnerable and the hardest-hit age group [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study that had addressed the prevalence of PTSD among COVID recovered patients found that nearly 20% of these patients had symptoms of post-traumatic stress 1 month following hospitalization [ 7 ]. However, this study does not have a good representation of older adults above 65 years, who are the most vulnerable and the hardest-hit age group [ 7 , 8 ]. Current literature on PTSD primarily focuses on stressors like physical assault, sexual violence, war, accident, kidnapping, and being threatened with a weapon, as the causative triggers of PTSD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%